Tinjauan Yuridis terhadap Pengaruh Penerapan Hak Tanggungan terhadap Lembaga Jaminan Hak Atas Tanah - Nur Asmidah Nasution; Dikko Ammar (Inovasi Pratama Internasional. Ltd, 2023)
The implementation mechanism for granting Mortgage Rights Electronically for Creditors and PPATs always begins with the making of the Deed of Granting Mortgage Rights (APHT) before the PPAT between the Mortgage Giver (usually Debtors) and Creditors (usually Banks). The APHT has met the qualifications as an Authentic Deed both in terms of Procedure, Substance and Authority of the PPAT who made it official. The APHT is then registered by the PPAT at the local Land Office electronically no later than 7 days after the APHT is inaugurated which forms the basis for the issuance of an Electronic Mortgage Certificate by the Land Office. The Mortgage Certificate is requested and printed by the Creditor Recipient of the Mortgage by paying the predetermined PNBP. The HT certificate can be printed by the creditor after 7 days since the APHT was registered by the PPAT. The resolution of problems and obstacles faced by Users of Electronic Mortgage Rights, especially PPATs and Creditors refers to the Technical Instructions made by the Ministry of ATR/KBPN, April 29 2020 because basically these problems and obstacles are mostly related to the IT system and the Electronic HT Service server. Users (PPAT and Creditors) must always confirm these IT problems to the Electronic HT service provider, namely the local Land Office, so that Users of Electronic Mortgage Services, in this case PPAT and Creditors must be skilled and adequate in using all the tools needed to complete the granting of Mortgage Rights until the issuance of the Electronic Mortgage Certificate.